Investigating the Relationship Between Mathematics Instructional Time and Perseverance Growth with Elementary Pre-Service Teachers - Joseph DiNapoli (Education Sciences)
This study investigated how the time that elementary pre-service teachers (PSTs) spend studying certain mathematics topics during a content course is related to growth in their perseverance in problem-solving. Using a quasi-experimental design, PSTs from two classes taught by the same instructor engaged in 12 problem-solving sessions each to measure their willingness to initiate and sustain, and re-initiate and re-sustain upon an impasse, productive struggle during engagement. Inspired by the thinking-oriented and knowledge-oriented theoretical approaches to teacher preparation in elementary mathematics, there were two class conditions. Over one semester, the treatment group studied five mathematics topics (averaging about 400 min of classroom time per topic) and the control group studied 10 mathematics topics (averaging about 150 min of classroom time per topic). The results show that the perseverance of PSTs in problem-solving in the treatment group grew at a significantly greater rate compared to PSTs in the control group. This suggests that PSTs’ perseverance development may be supported by spending more classroom time studying fewer topics during mathematics content courses.